Outcome in patients with small cell lung cancer re-irradiated for brain metastases after prior prophylactic cranial irradiation. (November 2016) - Bernhardt, Denise; Bozorgmehr, Farastuk; Adeberg, Sebastian; Opfermann, Nils; von Eiff, Damian; Rieber, Juliane; Kappes, Jutta; Foerster, Robert; König, Laila; Thomas, Michael; Debus, Jürgen; Steins, Martin; et al.
Highlights: Cerebral re-irradiation after prior PCI is beneficial in symptom palliation. Median OS after re-WBRT after prior PCI was 3 months. Median OS after SRS was 5 months. Re-irradiation is associated with minimal acute side effects. Abstract: Objectives: Patients with brain metastases from small-cell lung cancer (SCLC) who underwent prior prophylactic cranial irradiation (PCI) are often treated with a second course of whole brain radiation therapy (Re-WBRT) or stereotactic radiosurgery (SRS) for purposes of palliation in symptomatic patients, hope for increased life expectancy or even as an alternative to untolerated steroids. Up to date there is only limited data available regarding the effect of this treatment. This study examines outcomes in patients in a single institution who underwent cerebral re-irradiation after prior PCI. Methods: We examined the medical records of 76 patients with brain metastases who had initially received PCI between 2008 and 2015 and were subsequently irradiated with a second course of cerebral radiotherapy. Patients underwent re-irradiation using either Re-WBRT (88%) or SRS (17%). The outcomes, including symptom palliation, radiation toxicity, and overall survival (OS) following re-irradiation were analyzed. Survival and correlations were calculated using log-rank, univariate, and multivariate Cox proportional hazards-ratio analyses. Treatment-related toxicity was classified according to CTCAE v4.0. Results: Median OS of all patients was 3 months (range 0–12 months). Median OS after Re-WBRT was 3 months (range 0–12 months). Median OS after SRS was 5 months (range 0–12 months). Karnofsky performance status scale (KPS ≥50%) was significantly associated with improved OS in both univariate (HR 2772; p = 0, 009) and multivariate analyses (HR 2613; p = 0, 024) for patients receiving Re-WBRT. No unexpected toxicity was observed and the observed toxicity remained consistently low. Symptom palliation was achieved in 40% of symptomatic patients. Conclusions: In conclusion, cerebral re-irradiation after prior PCI is beneficial for symptom palliation and is associated with minimal side effects in patients with SCLC. Our survival data suggests that it is primarily useful in patients with adequate performance status.